Exploring the teaching and learning role of agricultural extension workers - Adrupio, Scovia (University of the Witwatersrand, Johannesburg, 2023)
Agricultural extension has been identified as a key occupation in many African countries. This is because extension workers play a critical role in linking farmers and other actors within the agricultural sector to policy and practice. As a result, teaching and learning are their most important roles. Agricultural extension systems and the work done by agricultural extension workers are faced with a number of challenges, including inadequate funding, a limited number of extension workers, climate change, and general changes in the agricultural system, to name a few. These changes call for extension workers to constantly change and adapt to the changes happening in their world of work in order to best assist farmers in addressing their challenges. Despite a large amount of research being conducted in different areas of agricultural extension, such as the training needs and requirements of extension workers, challenges facing agricultural extension, reforms in extension systems, and gender inequalities in extension, little work has focused on how their teaching and learning roles are changing. This study thus takes an in-depth look at the teaching and learning roles of agricultural extension workers. The study starts by conceptualising the agricultural extension occupation using the five dimensions of an occupation proposed by Shalem and Allais (2018) to unpack the different factors within each occupation and how these can impact the teaching and learning roles of agricultural extension workers. The results of the study provide an understanding of why occupations are social and political activities that are affected by a number of factors and are always undergoing changes. Studying changes in occupations is critical, as it enables us to understand changes in the world of work and how workers in the workplace adapt to work-related changes.
A research report being submitted for the Degree of Master of Education M.Ed (by Coursework and Research Report)at the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg. 2023.
Keywords: Agricultural extension; Teaching and learning roles; Occupations; Extension system; UCTD; SDG-8: Decent work and economic growth